Taking philosophy seriously - Amir, Lydia, 1955- (Cambridge Scholars Publishing, 2018)
Taking Philosophy Seriously initiates a meta-philosophical dialogue that challenges the division between academic and practical philosophy. In contradistinction to the perfectionist tradition of philosophy, it offers a melioristic view of philosophy that rethinks the approach to philosophy, reinvigorates its academic teaching and secures the respectability of its practitioners outside the academe. It addresses the neglected topic of philosophers education through a subtle analysis of the mentor-apprentice relationship and the remedies philosophers have found to its tensions. It reveals the problems inherent in emulating past practical philosophies from Alexandrian times, the Enlightenment or the 19th century, and the necessity of reevaluating the tools, reconsidering the means, and rethinking the methods of the contemporary practice of philosophy. To that purpose, it problematizes the notions of dialogue, self-knowledge, and self-transformation, and questions the feasibility of autonomy and self-integration as well as the differentiation between philosophy and psychology. It offers original solutions to the problems it highlights and points to unique benefits in the practice of philosophy that contribute to resolving the contemporary crisis of philosophy.This book combines high academic standards and an accessible style, and will engage academic and practical philosophers alike, professionals in education and the helping professions, and the general public. -- Provided by publisher.